Placental expression of 2,3 bisphosphoglycerate mutase in IGF-II knock out mouse: correlation of circulating maternal 2,3 bisphosphoglycerate and fetal growth. - Gu, M; Pritlove, D; Boyd, C; Vatish, M (2009)
Bisphosphoglycerate mutase (BPGM) catalyses the formation of 2,3 bisphosphoglycerate (BPG) a ligand of haemoglobin. BPG facilitates liberation of oxygen from haemoglobin at low oxygen tension enabling efficient delivery of oxygen to tissues. We describe expression of BPGM in mouse labyrinthine trophoblasts, located at the maternal-placental interface. Expression is lower in placentae of igf2(+/-) knockout mice, a widely used model of growth restriction, compared to wild type placentae. Circulating maternal BPG increased throughout gestation but this increase was less in wt mothers carrying igf2(+/-) pups than in those carrying exclusively wt pups. This reduction was observed well before term and may contribute to the low birth weight of igf2(+/-) pups. Strikingly, we also measured reductions of fetal and placental weight in wt littermates of igf2(+/-) pups compared to pups developing in an exclusively wt environment. These data suggest that placental expression of BPGM can influence maternal BPG concentrations and supports a hypothesis under which BPG synthesized in the placenta may act on maternal haemoglobin to enhance delivery of oxygen to the developing fetus.